2021
DOI: 10.1111/bcp.14877
|View full text |Cite
|
Sign up to set email alerts
|

Prior use of therapeutic anticoagulation does not protect against COVID‐19 related clinical outcomes in hospitalized patients: A propensity score‐matched cohort study

Abstract: The hypercoagulable state observed in COVID-19 could be responsible for morbidity and mortality. In this retrospective study we investigated whether therapeutic anticoagulation prior to infection has a beneficial effect in hospitalized COVID-19 patients. This study included 1154 COVID-19 patients admitted to 6 hospitals in the Netherlands between March and May 2020. We applied 1:3 propensity score matching to evaluate the association between prior therapeutic anticoagulation use and clinical outcome, with in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
3
21
1
Order By: Relevance
“…Hence, the role of prior OAC therapy in the context of COVID-19 is gaining interest. For example, a recent study concluded that prior use of therapeutic anticoagulation was not associated with improved survival in hospitalized COVID-19 patients [ 39 ]. Similarly, a small study found that regular VKA use in hospitalized frail older patients with COVID-19 was associated with increased mortality during the first week [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the role of prior OAC therapy in the context of COVID-19 is gaining interest. For example, a recent study concluded that prior use of therapeutic anticoagulation was not associated with improved survival in hospitalized COVID-19 patients [ 39 ]. Similarly, a small study found that regular VKA use in hospitalized frail older patients with COVID-19 was associated with increased mortality during the first week [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies 4,5,9,10,12-14 focusing on prehospital use of anticoagulants and one study 29 focusing on therapeutic use of anticoagulants found no difference in risk of mortality, mechanical ventilation or acute distress respiratory syndrome. Notably, some were of small sample size 4,[12][13][14] , with unclear exposure definition 5 , classifying patients who initiated therapeutic anticoagulation on day 3 or later after ICU admission in the control group 29 or used composite outcomes 9,10 , limiting the interpretation of the results. Two cohort studies showed a higher risk of admission to ICU, intubation, or death associated with anticoagulants in patients with COVID-19 disease, compared with non-use, but the results were possibly due to confounding by indication.…”
Section: Findings In Contextmentioning
confidence: 99%
“…[1][2][3] While anticoagulants appear to be a useful treatment option for hospitalised patients with COVID-19, most studies investigated the potential protective role of routine use of oral anticoagulants (OACs) in COVID-19 related outcomes were of small sample size or in hospital setting only. [4][5][6][7][8][9][10][11][12][13][14] Notably, people taking oral anticoagulants are likely to have more comorbidities than those not, and so comparing COVID-19 outcomes for OAC use with no use could be subject to confounding. Importantly, use of OAC treatment is partly threshold based; according to the guidelines for the management of patients with atrial fibrillation (AF), which is also one of the Quality and Outcome Framework indicators a payment incentive scheme in English general practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, it soon became clear that patients continued to have thrombotic events on prophylactic heparin (Trimaille et al, 2020) and some studies suggested that using intermediate dose heparin was more effective (Stessel et al, 2020;Meizlish et al, 2021a) although other studies showed no benefit from the increased dose of heparin (Investigators, 2021). One study found that therapeutic anticoagulation in COVID-19 patients reduced the risk of pulmonary embolism but had no effect on mortality (Spiegelenberg et al, 2021). This is reminiscent of bacterial sepsis where anti-coagulants such as activated protein C and heparin provided some benefit but never really resolved the issue.…”
Section: Covid-19 and Thrombosismentioning
confidence: 99%